2017
DOI: 10.4314/ejesm.v9i2.5s
|View full text |Cite
|
Sign up to set email alerts
|

Economic sustainability of sheabutter production in Kwara state, Nigeria

Abstract: Production of sheabutter has the economic potentials in sustaining income

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…The result further revealed that majority (65.8%) of the respondents had Shea butter production as their major means of livelihood. This agrees with the findings of Ibrahim et al (2016) who indicated that about 95% of the processors are involved in Shea nuts processing on fulltime basis in Nigeria.…”
Section: Socio-economic Demographics Of the Respondentssupporting
confidence: 92%
“…The result further revealed that majority (65.8%) of the respondents had Shea butter production as their major means of livelihood. This agrees with the findings of Ibrahim et al (2016) who indicated that about 95% of the processors are involved in Shea nuts processing on fulltime basis in Nigeria.…”
Section: Socio-economic Demographics Of the Respondentssupporting
confidence: 92%